Fishing Condition and Fishers Income: The case of Lake Tana, Ethiopia - Dagninet Amare; Mihret Endalew; Tegegne Debas; Ayalew Demissew; Kiber Temesgen; Ayenew Meresa; Amare Getnet (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2018)
Fishery provides a multitude of benefits ranging from employment to food security. Investigating the factors affecting fishing income and the fishing environment are crucial entry points for efficiency maximization intervention. A survey was conducted in all Woredas' adjacent to Lake Tana. Data was gathered using household survey and focus group discussions and analyzed by a linear regression model. The results indicated that the fishery in Lake Tana is comprised of diverse individuals in relation to occupation, engagement intensity and membership to cooperatives. Fish related income was positively correlated to years of schooling and ownership of motorized boat while negatively correlated to membership to fish cooperatives. Interventions aimed at improving the market infrastructure, delivery of major fishery inputs, training on processing and use of by-products, revising the membership requirements and enforcement of fishery related laws are critical for sustainability of the fishery resource.